Keterlibatan Ayah dalam Pengasuhan Anak Berkebutuhan Khusus: Studi Kasus - Istiqomah, Riska Dwi; Laili, Nurfi; Affandi, Ghozali Rusyid (Universitas Muhammadiyah Magelang, 2026)
Father involvement is crucial for children's emotional, social, and cognitive development, but their role in parenting children with special needs remains minimal. This study explores the forms and dynamics of father involvement in parenting children with special needs, focusing on factors that influence father involvement in parenting: emotional, cognitive, social, and behavioral factors. This study examines the forms and dynamics of fathers' involvement in the care of children with special needs, focusing on the emotional, cognitive, social, and behavioral factors that influence fathers' involvement in childcare. This study uses a qualitative case study approach with purposive sampling, based on the criteria of fathers who have children with special needs aged 4 years or older. Data were collected through in-depth semi-structured interviews and participatory observation, followed by thematic analysis to identify patterns and meanings in the fathers' experiences. Emotionally, fathers experienced shock, denial, and fear, which hindered the development of the father-child relationship. Cognitively, fathers tended to delegate child-rearing responsibilities to mothers. Socially, stigma and shame caused fathers to withdraw from society. Behavioral involvement was inconsistent and generally limited to simple activities. Significant barriers included traditional gender roles, workload, lack of information, and lack of social support. The results of this study highlight the importance of comprehensive family interventions, such as education programs, parenting classes, and psychological counseling, to increase father involvement. Gender-sensitive policies are also needed to create an inclusive environment in the care of children with special needs.